Real-Virtual Objects: Exploring Bidirectional Embodied Tangible Interaction with a Virtual Human in World-Fixed Virtual Reality - Bozgeyikli, Lal lLilar (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2024)
In everyday interactions with others, we often affect each other's space through shared physical objects. Despite the commonality of such bidirectional interactions in real life, few have explored this form of interaction in virtual reality. This paper explores bidirectional embodied tangible interaction between a human and a virtual human through shared objects that span the real-virtual boundary in world-fixed virtual reality. The shared objects extend from the real world into the virtual world (and vice versa). We discuss the novel interaction concept and implementation details and present the results of a between-subjects user study with 40 participants where we compared the developed novel real-virtual shared object interaction with a control version where the shared objects were separated as completely physical and virtual. In summary, the results showed that presence and co-presence were increased with the real-virtual object interaction, along with affective attraction to the virtual human and enjoyment of interaction.